Sex-based harassment and organizational silencing: How women are led to reluctant acquiescence in academia. (October 2019) - Fernando, Dulini; Prasad, Ajnesh
The #MeToo and the Time's Up movements have raised the issue of sexual harassment encountered by women to the level of public consciousness. Together, these movements have captured not only the ubiquity of sexual harassment in the everyday functioning of the workplace, but they have also demonstrated how women are silenced about their experiences of it. Inspired by the political and the social currents emerging from these movements, and theoretically informed by ideas of discursive hegemony, rhetorical persuasion and affective practice, this article draws on a qualitative study of early- and mid-career female academics in business schools to answer the following question: How are victims who start to voice their experiences of sex-based harassment silenced within the workplace? Our findings reveal that organizational silence is the product of various third-party actors (e.g. line managers, HR, colleagues) who mobilize myriad discourses to persuade victims not to voice their discontent. We develop the concept of 'reluctant acquiescence' to explain the victims' response to organizational silencing. In terms of its contributions to the extant literature, this article: (i) moves away from explanations of sex-based harassment that focus solely (or predominately) on the actions of individual perpetrators; and (ii) shows how reluctant acquiescence leads to maintaining the status quo in the organization. In highlighting features of academic work that facilitate reluctant acquiescence, we call for more contextualization of the dynamics of sex-based harassment specifically, and other forms of workplace mistreatment broadly.